Pain referral patterns of the C1 to C3 nerves: Implications for headache disorders - Mollie Johnston; Sheldon E. Jordan; Andrew Charles (2013)
The cervical nerves may play a significant role in primary headache disorders. We reviewed the patterns of pain evoked by stimulation of the first 3 cervical nerves (C1-C3) in 10 patients with chronic occipital pain, 6 of whom also had migraine. Stimulation at the C1 level evoked periorbital and frontal pain in 6 of 6 patients with migraine but evoked occipital or cervical pain in those without migraine. C2 and C3 stimulation resulted in occipital or cervical pain in all patients. The C1 nerve may have an important sensory function in headache disorders that have orbital and frontal pain as a prominent feature.